2011
DOI: 10.1111/j.1600-0412.2011.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden of testing positive for high-risk human papillomavirus on women with atypical cervical cytology: a prospective study

Abstract: A concurrent positive HPV result intensified the distress of women with ASCUS at result notification. With time and after colposcopy, their initial heightened anxiety and cervical cancer worry were significantly lowered. However, HPV positivity may pose a prolonged psychosocial burden on women even after having had the necessary follow-up for their cervical abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 25 publications
5
47
2
1
Order By: Relevance
“…Studies in women with low-grade abnormal cytology results, who may already have elevated anxiety from learning of these results, have reported similar findings. In these studies, anxiety, distress, and intrusive thoughts were also more common in HPV-positive women than those testing negative [8], [11]. In studies comparing women with normal and abnormal cytology, however, a greater difference in anxiety and psychological distress was observed between HPV-positive and HPV-negative women in the group with normal cytology than in those with abnormal results [9], [12].…”
Section: Introductionmentioning
confidence: 82%
“…Studies in women with low-grade abnormal cytology results, who may already have elevated anxiety from learning of these results, have reported similar findings. In these studies, anxiety, distress, and intrusive thoughts were also more common in HPV-positive women than those testing negative [8], [11]. In studies comparing women with normal and abnormal cytology, however, a greater difference in anxiety and psychological distress was observed between HPV-positive and HPV-negative women in the group with normal cytology than in those with abnormal results [9], [12].…”
Section: Introductionmentioning
confidence: 82%
“…First-trimester Pap smears are part of the routine prenatal screening programs in most countries, and abnormal cervical cytology results may cause psychological distress [7]. The prevalence rate does not differ from nongravid women and is estimated to range from 5 to 20% [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic accuracy of prenatal cytology and colposcopy can be reduced by pregnancy-related changes [3,6]. Uncertainty about the diagnosis and the further clinical course is likely to be of concern for the obstetrician and causes psychological distress in pregnant women [7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, it appears that interventions designed to mitigate disease-associated distress are underutilized or ineffective, as patients frequently report worsening anxiety during the course of their treatment [71]. Consider also that women with HPV-associated cervical dysplasia or invasive carcinoma may suffer from feelings of confusion, fear, and guilt in response to their diagnosis [72, 73]. It has also been demonstrated that feelings that contribute to self-blame and isolation may negatively affect information-seeking behaviors during physician–patient interactions, and may impair patient adherence to treatment recommendations [74].…”
Section: Hpv Testing In Hnc: Rationale For Testing and Patient Counsementioning
confidence: 99%